Junie B., first grader : cheater pants - Park, Barbara; Brunkus, Denise (New York : Random House, 2003)
When her father will not let her stay up late to do her homework, first grader Junie B. copies a classmate's paper.
"A Stepping Stone Book."
Keywords: Cheating; Schools; Humorous stories